A monolithic artificial iconic memory based on highly stable perovskite-metal multilayers - Guan, Xinwei (2021)
Artificial iconic memories, also called photomemories, are new types of nonvolatile memory that can simultaneously detect and store light information in a monolithic device. Several approaches have been proposed to construct artificial iconic memories, such as three-terminal field effect transistors, which can achieve an effective control of the gate voltage and external light terminals. The drawbacks in constructing these memories involve complicated fabrication processes, and the resulting performance of, for example, perovskite transistor-type photomemories is limited by the low carrier mobilities and poor ambient stabilities, whereas architectures based on floating gate modulations entail strict interface engineering and poor device reliability. In this paper, we propose a novel monolithic artificial iconic memory with a multilayer architecture of indium tin oxide/perovskite/gold/perovskite/silver, which combines the memory and photodetector functionalities of perovskites in an integrated device. The bottom perovskite layer plays the role of a photodetector, modulating the voltage bias on the top perovskite layer that serves as a resistive switching memory. This multilayer perovskite device can store photo-sensing data in its resistive states, with a memory retention of 5 × 103 s and ambient stability longer than sixty days. As a prototype demonstration, a 7 × 7 artificial iconic memory array is constructed to detect and store data on light intensity distribution, enabling a nonvolatile imaging functionality. Our work provides a new platform for designing perovskite-based architectures with simultaneous light detection and data storage capabilities.